Prática mental orientada a tarefas funcionais na recuperação de indivíduos com acidente vascular encefálico - Clarissa Cardoso dos Santos Couto Paz (2012)
Mental practice (MP) is a cognitive strategy, which may benefit the acquisition of motor skills and functional performance of athletes and individuals with neurological injuries. The purpose of this study was to evaluate whether individualized, specific functional task-oriented MP, when added to conventional physical therapy (PT), promoted better learning of motor activities of daily living (ADL) in individuals with chronic stroke (13 ± 6.5 months of onset of the stroke). Nine people with stable mild and moderate upper limb impairments were evaluated, by employing an A1-B-A2 single-case design. Phases A1 and A2 included one month of conventional physical therapy (PT) and phase B the addition of MP training to PT. The motor activity log (MAL-Brazil) was employed to assess the amount of use (AOU) and quality of movement (QOM) of the paretic upper limb in daily functions; the revised motor imagery questionnaire (MIQ-RS) was used to assess the abilities in kinesthetic and visual motor imagery; the Minnesota manual dexterity test to assess manual dexterity; and gait speed to assess mobility. After phase A1, no significant changes were observed for any of the evaluated measures. However, after phase B, significant improvements were observed for both the MAL AOU and QOM scores (p<0.0001, for both), for both MIQ-RS kinesthetic and visual scores (p=0.003; p=0.007, respectively), for manual dexterity (p=0.002) and gait speed (p=0.019). In addition, clinically significant gains in ADL were observed. Functional specific task-oriented MP, when added to conventional PT, led to improvements in motor imagery abilities associated with increases in the AOU and QOL during ADL.